Transcatheter microwave ablation can deliver deep and circumferential perivascular nerve injury without significant arterial injury to provide effective renal denervation. Issue 10 (October 2019) - Qian, Pierre C.; Barry, Michael A.; Lu, Juntang; Al-Raisi, Sara; Mina, Ashraf; Ryan, Joshua; Bandodkar, Sushil; Alvarez, Shirley; James, Virginia; Ronquillo, John; Varikatt, Winny; Clayton, Zoe; et al.
Abstract : Background: Clinical studies of transcatheter radiofrequency renal denervation for treating hypertension have been hampered by the lack of consistent denervation efficacy. We aimed to demonstrate the short-term efficacy and safety of transcatheter microwave renal denervation. Methods: A novel 7F microwave system was validated in a sheep model of unilateral renal denervation. Up to two microwave ablations were delivered to each artery with maximum power at 100–110 W for 480 s. Results: Catheter deployment and ablation was successful in all 19 targeted vessel segments, and ablation produced substantial circumferential perivascular injury; median ablation lesion area greater than 395 [interquartile range (IQR) 251–437] mm 2, depth 17.1 (IQR 15.8–18.4) mm, length 16 (IQR 12–20) mm, without collateral visceral injury. Limiting power to 100 W minimized arterial injury, while maintaining a deep circumferential perivascular ablation. Microwave denervation reduced median functional sympathetic nerve surface area at the renal hilum on antityrosine hydroxylase staining by 100% (IQR 87–100%, P  = 0.0039), and median renal cortical norepinephrine content by 83% (IQR 76–92%, P  = 0.0078), compared to the paired control kidney at 2–3 weeks postprocedure. Conclusion: Transcatheter microwave ablation can produce deep circumferential perivascular ablations over a long segment of the renal artery without significant arterial or collateral visceral injury to provide effective renal denervation.